KOMPETENSI PERADILAN TATA USAHA NEGARA TERHADAP PENGAWASAN PENYELENGGARAAN PEMERINTAHAN DITINJAU DARI PERLUASAN ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN - Melissa Silalahi, Devi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2020)
This article discusses Administrative Court’s control function in governance toward implementation of government’s duties. As we know, Administrative Court has its role to resolve any administrative disputes between government and citizens. The aims of this article is to know deeply the competency of Administrative Court after the enactment of Law Number 30 Year 2014 about Government Administration as the law regulates main material sources of state administrative law. This is due to the addition of general principles of good governance’s types to file a tort claim for an unlawful act committed by government. Moreover, general principles of good governance become a legal instrument for Judges of State Administration Court to review the legality of any decision of State Administration. In the Article 10 Law Number 30 Year 2014 is stated that there are eight types general principle of good governance. However, Judges has a right to look broader and find another types beyond that eight in order to make legal decision. Therefore, Law Number 30 Year 2014 becomes foundation of the main material law of state administrative procedure law. In the other hand, Law Number 30 Year 2014 requires government to publish every administrative decree based on provisions in law and general principles of good governance.